The combination of metformin and high glucose increased longevity of Caenorhabditis elegans a DAF-16/FOXO-independent manner: cancer/diabetic model via C. elegans - Berk, Şeyda; Cetin, Ali; Özdemir, Özgür Ülkü; Pektaş, Ayşe Nur; Yurtcu, Nazan; Dastan, Sevgi Durna (Frontiers in Endocrinology, 2024)
Sedentary lifestyles and diets with high glycemic indexes are considered to be contributing factors to the development of obesity, type 2 diabetes in humans. Metformin, a biguanide medication commonly used to treat type 2 diabetes, has been observed to be associated with longevity; however, the molecular mechanisms underlying this observation are still unknown. The effects of metformin and high glucose, which have important roles in aging-related disease such as diabetes and cancer, were studied in lin-35 worms because they are associated with cancer-associated pRb function in mammals and have a tumour suppressor property. According to our results, the negative effect of high glucose on egg production of lin-35 worms was greater than that of N2 worms. High glucose shortened lifespan and increased body length and width in individuals of both strains. Metformin treatment alone extended the lifespan of N2 and lin-35 worms by reducing fertilization efficiency. However, when metformin was administered in the presence of high glucose, the lifespan of lin-35 worms was clearly longer compared to N2 worms. Additionally, we conclude that glucose and metformin in lin35 worms can extend life expectancy through a DAF-16/FOXO-independent mechanism. Furthermore, the results of this study will provide a new perspective on extending mammalian lifespan through the model organism C. elegans.